A Study on Mineral Status of Murrah Buffaloes in Charkhi Dadri District of Haryana - Ramsawroop; V.S. Panwar; Sandeep Kumar; Sushil Kumar (Indian Journal of Animal Nutrition, 2022)
A detailed survey was carried out to record feeding plane and mineral status of lactating buffaloes in Charkhi Dadri district of Haryana state during rabi season. Samples of feedstuffs, milk, hair and blood were collected from ten families of 12 villages (3 villages from each of 4 blocks) thus making a total of 120 families. Berseem as a green fodder was fed to the buffaloes by most of the livestock owners (73.3%) followed by oat fodder. Among dry roughages; wheat straw (90.8%), bajra kadbi (17.5%) and rice straw (23.3%) were fed. Among cereals, wheat was used by 76.7% of farmers followed by bajra grain (44.2 %). Cotton seed cake (75%) and cotton seed (47.5%) were popular protein supplements in the dietary regimen of buffaloes. among the farmers. Only 17.5 and 13.3% of farmers were supplementing mineral mixture and common salt to their animals respectively. Regarding intake of mineral, it was found that almost all the animals were consuming much less Zn and Cu than their requirement while intake of Iron was more than the requirement. Only 10.8% and 15% of the animals were receiving less Ca and P, respectively, than their requirement. Average value of serum Zn in most of the samples was within normal range i.e., 0.8 to 2 ppm while that of serum Cu was below critical level. Intake of Fe was high due to high content in feed and fodders still its level in serum was within the normal range. Serum Mn was above critical value (0.20 ppm) while Ca and P were marginally deficient. Hair and milk samples were deficient in Zn and Cu. All milk samples had Fe concentration above the critical level (0.3 ppm).